2022
DOI: 10.1039/d2ta04418h
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating the reaction kinetics of lithium–oxygen chemistry by modulating electron acceptance–donation interaction in electrocatalysts

Abstract: Lithium-oxygen batteries (LOBs) have presented great promise in next-generation energy storage systems due to their high theoretical energy density. However, the sluggish deposition and decomposition kinetics of lithium peroxide (Li2O2)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Simultaneously, the single electron on d yz orbital of Ti 3+ can hop into anti‐bonding π 2p (π 2p *) orbitals for accomplishing the electron donation owing to the half‐filling state of π 2p * orbital of O 2 , which strengthens the binding between active Ti 3+ sites and adsorbed oxygen. [ 37–39 ] During the process, TiO bond coupling is enhanced, which can explain the effective activation of O 2 on the surface of N‐Ti 3 C 2 (H) and N‐Ti 3 C 2 (A). Due to the relatively large proportion of Ti 3+ species in N‐Ti 3 C 2 (H), the maximum discharge capacity is delivered.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneously, the single electron on d yz orbital of Ti 3+ can hop into anti‐bonding π 2p (π 2p *) orbitals for accomplishing the electron donation owing to the half‐filling state of π 2p * orbital of O 2 , which strengthens the binding between active Ti 3+ sites and adsorbed oxygen. [ 37–39 ] During the process, TiO bond coupling is enhanced, which can explain the effective activation of O 2 on the surface of N‐Ti 3 C 2 (H) and N‐Ti 3 C 2 (A). Due to the relatively large proportion of Ti 3+ species in N‐Ti 3 C 2 (H), the maximum discharge capacity is delivered.…”
Section: Resultsmentioning
confidence: 99%
“…The decreased overpotential is favorable for inhibiting the formation of by‐products, thereby enhancing the cycling stability of the Li‐O 2 battery. [ 37 ] As shown in Figure 3h, long‐term cyclic stability test with the cut‐off capacity of 500 mA h g −1 was carried out with current density of 200 mA g −1 . It can be found that N‐Ti 3 C 2 (H) can run stably for 372 cycles, which is far more than the N‐Ti 3 C 2 (A) electrode (199 cycles) and Ti 3 C 2 electrode (152 cycles).…”
Section: Resultsmentioning
confidence: 99%
“…Solution‐mediated mechanism: when the cathode catalyst has weak adsorption, the intermediate product LiO 2 generated by O 2 reduction solvates and diffuses into the electrolyte. As the reaction proceeds, the LiO 2 (sol) aggregated in the electrolyte undergoes further disproportionation reactions, resulting in the formation of toroidal Li 2 O 2 [69–71] . O2+e-+Li+LiO2(sol) $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr {\rm O}{_{2}}+{\rm e}{^{- }}+{\rm Li}{^{+}}\rightarrow {\rm LiO}{_{2}}({\rm sol})\hfill\cr}}$ 2LiO2(sol)Li2O2+O2 $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr {\rm 2LiO}{_{2}}({\rm sol})\rightarrow {\rm Li}{_{2}}{\rm O}{_{2}}+{\rm O}{_{2}}\hfill\cr}}$ …”
Section: Fundamental Spinel‐type Electrocatalysts In Lobsmentioning
confidence: 99%
“…As the reaction proceeds, the LiO 2 (sol) aggregated in the electrolyte undergoes further disproportionation reactions, resulting in the formation of toroidal Li 2 O 2 . [69][70][71] O…”
Section: Fundamental Spinel-type Electrocatalysts In Lobs 21 Mechanis...mentioning
confidence: 99%
“…[4] Given the dramatically improved theoretical energy density, advanced Li metal batteries (LMBs), such as Li-oxygen (Li-O 2 ) (≈3505 Wh kg −1 ) and Li-sulfur (Li-S) (≈2600 Wh kg −1 ) batteries, are in the spotlight. [5][6][7][8][9][10] So far, practical gravimetric energy densities of Li-lithium transition-metal oxide (Li-LMO), Li-S, and Li-O 2 batteries can achieve ≈440 Wh kg −1 , ≈650 Wh kg −1 and ≈950 Wh kg −1 , respectively, surpassing that of commercialized LIBs.Notably, the Li-O 2 batteries owning a high volumetric energy density (≈1100 Wh L −1 ) is on a par with petrol (≈1200 Wh L −1 ) (Figure 1a). [11] Since 2010s, chasing higher energy density boosts the rapid development of LMAs (Figure 1b) and exponentially increasing scientific researches (Figure 1c).…”
mentioning
confidence: 99%